The relative age effect in male and female English age-grade rugby union: Exploring the gender-specific mechanisms that underpin participation. Issue 3 (3rd July 2022) - Kelly, Adam L.; Jackson, Daniel T.; Barrell, Donald; Burke, Kate; Till, Kevin
ABSTRACT: The relative age effect (RAE) is a phenomenon that represents how young athletes who are born early in the selection year are often overrepresented within youth sport settings. The contact nature of rugby union may further magnify the physiological advantages of those athletes who are chronologically older. Thus, the purpose of this study was to examine the RAE within English age-grade rugby union. Male ( n = 228, 206) and female ( n = 23, 563) English age-grade rugby union participants were allocated into their 12-month annual age-category (under-7 to under-18). Data was analysed using a chi-square goodness-of-fit test to compare the observed and expected distributions. Significant differences were revealed in all male ( p < 0.001) and nine out of twelve female ( p < 0.05) annual-age categories. From a male perspective, a higher relative difference became present at under-14 onwards, suggesting that there may be further implications due to the onset of puberty and the introduction of 15-a-side competition. Further female analysis revealed that there was a within-2-year effect in their 24-month age groups (under-13 and under-15). Interestingly, there was an inverse within-3-year effect (i.e., an overrepresentation of younger players) within the female 36-month age group (under-18). The key findings indicate a RAE has become ingrained in English age-grade rugby union, as well as outlining important gender-specific considerations.